MiR-199a-3p inhibits proliferation and induces apoptosis in rheumatoid arthritis fibroblast-like synoviocytes via suppressing retinoblastoma 1. Issue 6 (14th November 2018) - Wangyang, Yufan; Yi, Linhong; Wang, Tao; Feng, Yanbo; Liu, Guangwang; Li, Dongya; Zheng, Xin
Abstract : Background Fibroblast-like synoviocytes (FLSs) that line the intimal synovium play a crucial role in the pathogenesis of rheumatoid arthritis (RA). miR-199a-3p is a highly conserved miRNA that has been shown to regulate a variety of growth behaviors in diverse cell types. However, the role of miR-199a-3p in RA-FLS is still unknown.Methods Here, we presented the first experimental evidence showing that miR-199a-3p was a critical regulator of RA-FLS function.Results miR-199a-3p expression was significantly reduced in RA-FLS compared with normal FLS. Ectopic expression of miR-199a-3p significantly inhibited RA-FLS proliferation and induced apoptosis, which was demonstrated by an increase in caspase-3 activity and Bax/Bcl-2 ratio. Our bioinformatics analysis identified Retinoblastoma 1 ( RB1 ) gene to be a direct target of miR-199a-3p. In RA-FLS, miR-199a-3p directly targetted the 3′-UTR of RB1 mRNA and suppressed endogenous RB1 expression, whereas miR-199a-3p-resistant variant of RB1 was not affected. Silencing RB1 decreased cell proliferation and promoted apoptosis in RA-FLS, an effect comparable with miR-199a-3p overexpression. Enforced expression of RB1 partially restored cell proliferation and attenuated apoptosis in miR-199a-3p-overexpressing RA-FLSs.Conclusion In summary, miR-199a-3p is down-regulated in RA-FLS, and miR-199a-3p inhibits proliferation and induces apoptosis in RA-FLS, partially via targetting RB1. The miR-199a-3p/RB1 pathway may represent a new therapeutic target for RA.